FORMULATION AND IN VITRO SPF EVALUATION OF BREADFRUIT LEAVES [Artocarpus altilis (Parkinson) Fosberg] SUNSCREEN CREAM - Putri, Yola Desnera; Trilestari, Rostika Dewi; Fitri, Yova Amijaya (Sekolah Tinggi Farmasi Indonesia, 2021)
Sunscreen, also known as sunblock, is a photoprotective topical product for the skin that absorbs or reflects some of the sun's ultraviolet radiation and thus helps protect against sunburn. Breadfruit leaves are one of the natural substances that could be used as sunscreen. It contains flavonoids, which may help to protect against the detrimental effects of UV rays. The goal of this study is to determine the formula of a sunscreen cream made from breadfruit leaves extract that meets excellent physical quality standards, as well as the results of an in vitro SPF value test using breadfruit leaves extract as a sunscreen cream preparation. The study was designed as a laboratory-based experiment. Breadfruit leaves extract prepared using the reflux method was employed in this study. Furthermore, the viscous extract was transformed into a sunscreen cream, which was then evaluated either physically or by calculating the SPF value. The results showed that breadfruit leaves extract at 200 ppm had an SPF of 19.023 in the ultra protection category while the sunscreen cream had an SPF of 18.624 in the ultra protection category at a concentration of 10.000 ppm. The UV protection of the sunscreen cream made from breadfruit leaves extract is excellent. Keywords: Breadfruit leaves, cream, sunscreen, SPF